Gestion administrativa y su relacion con la recuperacion de carrera vencida del segmento de microcréditos, del Banco Nacional de Fomento canton El Empalme, primer semestre del 2013 - Carrera Aguayo, Erwin Yamil (2013)
The investigation determined that the prices, natural disasters and investment diversions affect the customer default in microcredit National Development Bank Branch El Empalme. Since this is a public financial institution to promote and develop autonomous, with legal personality, its own assets and indefinite duration with this research project the Administrative Management of the National Development Bank in Canton El Empalme and its relation to recovery was assessed PDL Microcredit segment because this is by studying the origin of NPLs in the collection of overdue loans given in the institution; is why this work is aimed to know what were the causes that led to the maturity of the transaction; This will help to determine whether the Branch is on right track with regard to recovery management. Also describes globally the problem of the branch in this area which is the improper placement of microcredit them that cause NPLs recovery emerging segment is justified in that the subject is of interest that contribute to improving the management of grant and recovery of microcredit in the institution, for a more accurate description describe concepts, laws, relevant policies related to the topic under study, defined by a methodology that evaluates and explains the methods used by simple language. Analyzed the results it was determined that applying more control of each microcredit granted, may minimize the risk of default of the same which will allow the agency meet its objectives and goals towards the integral development..